Influence of soft block and film thickness on confined morphology of poly(ether‐mb‐amide) multiblock copolymers. Issue 1 (28th January 2020) - Cao, Yiyu; Zhu, Ping; Zhou, Yong; Wang, Dujin; Dong, Xia
Abstract: This work investigated the confined morphology within ultrathin films of a family of poly(ether‐ mb ‐amide) multiblock copolymer (PEAc) samples, which contains long‐chain carbon polyamide 1012 (PA1012) and poly(tetramethylene oxide) (PTMO). As a weakly segregated system, the PA1012‐rich phase could break out the microdomains forged by the phase separation in the melt and big spherulites were observed after cooling. The PTMO segments and the film thickness were the key factors in determining the crystalline structure and morphology. As the content of PTMO component increased, an obvious morphological evolution was observed in the atomic force microscopy test. The morphological evolution was related to the increase of segregation strength and the dilution effect. The evolution of PA1012 crystalline structure along with the decreasing of film thickness resulted from the slow diffusion rate of crystallizable chains, the higher glass transition temperature, and the lower number of nuclei induced by the considerably thin film thickness. Abstract : The microphase separation and dilution effect by soft segments content and the confinements effect by low film thickness lead to the very different morphology of PA1012 crystalline phases.